Synthesis and bioactivity of pyrrole-conjugated phosphopeptides - Zhang, Qiuxin; Tan, Weiyi; Xu, Bing (Beilstein Journal of Organic Chemistry, 2022)
Here we report the synthesis and effect on the cell viability of pyrrole-conjugated phosphopeptides. Encouraged by the selective inhibition of cancer cells by a naphthyl-capped phosphopeptide (Nap-ffpy, 1), we conjugated the heteroaromatic dipyrrole or tripyrrole motif at the N-terminal of short peptides containing phosphotyrosine or phosphoserine and examined the bioactivity of the resulting phosphopeptides (2–10). Although most of the phosphopeptides exhibit comparable activities with that of 1 against HeLa cells at 200 μM, they, differing from 1, are largely compatible with HeLa cells at 400 μM. Enzymatic dephosphorylation of 2–10, at 400 μM is unable to induce a dramatic morphological transition of the peptide assemblies observed in the case of 1. These results suggest that a heteroaromatic motif at the N-terminal of peptides likely disfavors the formation of extensive nanofibers or morphological changes during enzymatic self-assembly, thus provide useful insights for the development of phosphopeptides as substrates of phosphatases for controlling cell fate.
Keywords: cells; enzyme; N-terminal; peptides; pyrroles; self-assembly

(untitled) - Acar, H.; Srivastava, S.; Chung, E. J.; Schnorenberg, M. R.; Barrett, J. C.; LaBelle, J. L.; Tirrell, M. (Adv. Drug Delivery Rev., 2017)

(untitled) - Kim, B. J.; Yang, D.; Xu, B. (Trends Chem., 2020)

(untitled) - Cheetham, A. G.; Chakroun, R. W.; Ma, W.; Cui, H. (Chem. Soc. Rev., 2017)

(untitled) - Ulijn, R. V.; Jerala, R. (Chem. Soc. Rev., 2018)

(untitled) - Gazit, E. (Chem. Soc. Rev., 2007)

(untitled) - Bietsch, J.; Olson, M.; Wang, G. (Gels, 2021)

(untitled) - Brito, A.; Abul-Haija, Y. M.; da Costa, D. S.; Novoa-Carballal, R.; Reis, R. L.; Ulijn, R. V.; Pires, R. A.; Pashkuleva, I. (Chem. Sci., 2019)

(untitled) - Gao, Y.; Kuang, Y.; Guo, Z.-F.; Guo, Z.; Krauss, I. J.; Xu, B. (J. Am. Chem. Soc., 2009)

(untitled) - Li, J.; Gao, Y.; Kuang, Y.; Shi, J.; Du, X.; Zhou, J.; Wang, H.; Yang, Z.; Xu, B. (J. Am. Chem. Soc., 2013)

(untitled) - Cheetham, A. G.; Zhang, P.; Lin, Y.-a.; Lock, L. L.; Cui, H. (J. Am. Chem. Soc., 2013)

(untitled) - Liang, C.; Yan, X.; Zhang, R.; Xu, T.; Zheng, D.; Tan, Z.; Chen, Y.; Gao, Z.; Wang, L.; Li, X.; Yang, Z. (J. Controlled Release, 2020)

(untitled) - Rele, S.; Song, Y.; Apkarian, R. P.; Qu, Z.; Conticello, V. P.; Chaikof, E. L. (J. Am. Chem. Soc., 2007)

(untitled) - Salick, D. A.; Kretsinger, J. K.; Pochan, D. J.; Schneider, J. P. (J. Am. Chem. Soc., 2007)

(untitled) - Chen, W.; Yang, S.; Li, S.; Lang, J. C.; Mao, C.; Kroll, P.; Tang, L.; Dong, H. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Hartgerink, J. D.; Beniash, E.; Stupp, S. I. (Science, 2001)

(untitled) - Lee, S.-Y.; Gao, X.; Matsui, H. (J. Am. Chem. Soc., 2007)

(untitled) - Burkoth, T. S.; Benzinger, T. L. S.; Urban, V.; Morgan, D. M.; Gregory, D. M.; Thiyagarajan, P.; Botto, R. E.; Meredith, S. C.; Lynn, D. G. (J. Am. Chem. Soc., 2000)

(untitled) - Silva, G. A.; Czeisler, C.; Niece, K. L.; Beniash, E.; Harrington, D. A.; Kessler, J. A.; Stupp, S. I. (Science, 2004)

(untitled) - Tang, J. D.; Mura, C.; Lampe, K. J. (J. Am. Chem. Soc., 2019)

(untitled) - Yang, Z.; Gu, H.; Fu, D.; Gao, P.; Lam, J. K.; Xu, B. (Adv. Mater. (Weinheim, Ger.), 2004)

(untitled) - Toledano, S.; Williams, R. J.; Jayawarna, V.; Ulijn, R. V. (J. Am. Chem. Soc., 2006)

(untitled) - Yang, Z.; Liang, G.; Guo, Z.; Guo, Z.; Xu, B. (Angew. Chem., Int. Ed., 2007)

(untitled) - Dragulescu-Andrasi, A.; Kothapalli, S.-R.; Tikhomirov, G. A.; Rao, J.; Gambhir, S. S. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, H.; Chen, P.; Wu, H.; Zou, P.; Wu, J.; Liu, Y.; Liang, G. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Chen, Z.; Chen, M.; Zhou, K.; Rao, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Nejadnik, H.; Ye, D.; Lenkov, O. D.; Donig, J. S.; Martin, J. E.; Castillo, R.; Derugin, N.; Sennino, B.; Rao, J.; Daldrup-Link, H. (ACS Nano, 2015)

(untitled) - Ye, D.; Shuhendler, A. J.; Cui, L.; Tong, L.; Tee, S. S.; Tikhomirov, G.; Felsher, D. W.; Rao, J. (Nat. Chem., 2014)

(untitled) - Hu, Y.; Zhang, J.; Miao, Y.; Wen, X.; Wang, J.; Sun, Y.; Chen, Y.; Lin, J.; Qiu, L.; Guo, K.; Chen, H.-Y.; Ye, D. (Angew. Chem., Int. Ed., 2021)

(untitled) - Yan, R.; Hu, Y.; Liu, F.; Wei, S.; Fang, D.; Shuhendler, A. J.; Liu, H.; Chen, H.-Y.; Ye, D. (J. Am. Chem. Soc., 2019)

(untitled) - Zhang, M.; Wang, C.; Yang, C.; Wu, H.; Xu, H.; Liang, G. (Anal. Chem. (Washington, DC, U. S.), 2021)

(untitled) - Chen, P.; Wang, H.; Wu, H.; Zou, P.; Wang, C.; Liu, X.; Pan, Y.; Liu, Y.; Liang, G. (Anal. Chem. (Washington, DC, U. S.), 2021)

(untitled) - Lin, Y.-X.; Qiao, S.-L.; Wang, Y.; Zhang, R.-X.; An, H.-W.; Ma, Y.; Rajapaksha, R. P. Y. J.; Qiao, Z.-Y.; Wang, L.; Wang, H. (ACS Nano, 2017)

(untitled) - Wang, C.; Du, W.; Zhang, T.; Liang, G. (Anal. Chem. (Washington, DC, U. S.), 2020)

(untitled) - Li, I.-C.; Hartgerink, J. D. (J. Am. Chem. Soc., 2017)

(untitled) - Zhou, J.; Du, X.; Gao, Y.; Shi, J.; Xu, B. (J. Am. Chem. Soc., 2014)

(untitled) - Feng, Z.; Wang, H.; Wang, S.; Zhang, Q.; Zhang, X.; Rodal, A. A.; Xu, B. (J. Am. Chem. Soc., 2018)

(untitled) - Wang, H.; Feng, Z.; Tan, W.; Xu, B. (Bioconjugate Chem., 2019)

(untitled) - Wang, H.; Feng, Z.; Wang, Y.; Zhou, R.; Yang, Z.; Xu, B. (J. Am. Chem. Soc., 2016)

(untitled) - He, H.; Wang, J.; Wang, H.; Zhou, N.; Yang, D.; Green, D. R.; Xu, B. (J. Am. Chem. Soc., 2018)

(untitled) - Zhou, L.; Lu, D.; Wang, Q.; Liu, S.; Lin, Q.; Sun, H. (Biosens. Bioelectron., 2017)

(untitled) - Liu, S.; Zhang, Q.; Shy, A. N.; Yi, M.; He, H.; Lu, S.; Xu, B. (J. Am. Chem. Soc., 2021)

(untitled) - Kuang, Y.; Miki, K.; Parr, C. J. C.; Hayashi, K.; Takei, I.; Li, J.; Iwasaki, M.; Nakagawa, M.; Yoshida, Y.; Saito, H. (Cell Chem. Biol., 2017)

(untitled) - Kuang, Y.; Shi, J.; Li, J.; Yuan, D.; Alberti, K. A.; Xu, Q.; Xu, B. (Angew. Chem., Int. Ed., 2014)

(untitled) - Feng, Z.; Han, X.; Wang, H.; Tang, T.; Xu, B. (Chem, 2019)

(untitled) - Zhou, J.; Du, X.; Yamagata, N.; Xu, B. (J. Am. Chem. Soc., 2016)

(untitled) - Tanaka, A.; Fukuoka, Y.; Morimoto, Y.; Honjo, T.; Koda, D.; Goto, M.; Maruyama, T. (J. Am. Chem. Soc., 2015)

(untitled) - Li, J.; Shi, K.; Sabet, Z. F.; Fu, W.; Zhou, H.; Xu, S.; Liu, T.; You, M.; Cao, M.; Xu, M.; Cui, X.; Hu, B.; et al. (Sci. Adv., 2019)

(untitled) - Yang, Z. M.; Xu, K. M.; Guo, Z. F.; Guo, Z. H.; Xu, B. (Adv. Mater. (Weinheim, Ger.), 2007)

(untitled) - Gao, J.; Zhan, J.; Yang, Z. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Yao, Q.; Huang, Z.; Liu, D.; Chen, J.; Gao, Y. (Adv. Mater. (Weinheim, Ger.), 2019)

(untitled) - Li, L.-L.; Liu, W.-J.; Cai, Q.; Wang, H. (J. Controlled Release, 2017)

(untitled) - Hu, X.; Yang, P.; He, J.; Liang, R.; Niu, D.; Wang, H.; Li, Y. (J. Mater. Chem. B, 2017)

(untitled) - Hu, L.; Li, Y.; Lin, X.; Huo, Y.; Zhang, H.; Wang, H. (Angew. Chem., Int. Ed., 2021)

(untitled) - Pires, R. A.; Abul-Haija, Y. M.; Costa, D. S.; Novoa-Carballal, R.; Reis, R. L.; Ulijn, R. V.; Pashkuleva, I. (J. Am. Chem. Soc., 2015)

(untitled) - Wang, H.; Shi, J.; Feng, Z.; Zhou, R.; Wang, S.; Rodal, A. A.; Xu, B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Yang, Z.; Liang, G.; Xu, B. (Acc. Chem. Res., 2008)

(untitled) - Zhou, J.; Xu, B. (Bioconjugate Chem., 2015)

(untitled) - Yang, Z.; Ma, M.; Xu, B. (Soft Matter, 2009)

(untitled) - Wang, H.; Feng, Z.; Del Signore, S. J.; Rodal, A. A.; Xu, B. (J. Am. Chem. Soc., 2018)

(untitled) - Feng, Z.; Wang, H.; Wang, F.; Oh, Y.; Berciu, C.; Cui, Q.; Egelman, E. H.; Xu, B. (Cell Rep. Phys. Sci., 2020)

(untitled) - Wang, H.; Feng, Z.; Xu, B. (Angew. Chem., Int. Ed., 2019)

(untitled) - Shi, J.; Du, X.; Yuan, D.; Zhou, J.; Zhou, N.; Huang, Y.; Xu, B. (Biomacromolecules, 2014)

(untitled) - Yang, D.; He, H.; Kim, B. J.; Xu, B. (Bioconjugate Chem., 2021)

(untitled) - Tan, W.; Zhang, Q.; Wang, J.; Yi, M.; He, H.; Xu, B. (Angew. Chem., Int. Ed., 2021)

(untitled) - He, H.; Liu, S.; Wu, D.; Xu, B. (Angew. Chem., Int. Ed., 2020)

(untitled) - Wang, H.; Feng, Z.; Xu, B. (J. Am. Chem. Soc., 2019)

(untitled) - Li, X.; Kuang, Y.; Lin, H.-C.; Gao, Y.; Shi, J.; Xu, B. (Angew. Chem., Int. Ed., 2011)

(untitled) - Dervan, P. B. (Bioorg. Med. Chem., 2001)

(untitled) - Reches, M.; Gazit, E. (Science, 2003)

(untitled) - Yang, Z.; Liang, G.; Ma, M.; Gao, Y.; Xu, B. (Small, 2007)

(untitled) - Wang, J.; Tan, W.; Li, G.; Wu, D.; He, H.; Xu, J.; Yi, M.; Zhang, Y.; Aghvami, S. A.; Fraden, S.; Xu, B. (Chem. – Eur. J., 2020)

(untitled) - Huang, A.; Ou, C.; Cai, Y.; Wang, Z.; Li, H.; Yang, Z.; Chen, M. (RSC Adv., 2016)

(untitled) - Naumann, T. A.; Naldrett, M. J.; Ward, T. J.; Price, N. P. J. (Protein Sci., 2015)

(untitled) - He, H.; Guo, J.; Xu, J.; Wang, J.; Liu, S.; Xu, B. (Nano Lett., 2021)

(untitled) - Yang, D.; Kim, B. J.; He, H.; Xu, B. (Pept. Sci., 2021)